KENASABAN KADAR 8-HYDROXY-2-DEOXYGUANOSINE (8-OHDG) SERUM DENGAN DERAJAT DEFISIT NEUROLOGIS PADA STROK ISKEMIK Correlation of Serum 8-Hydroxy-2-Deoxyguanosine (8-OHdG) With Neurological Deficits in Ischemic Stroke - Liza Liza; Ida Parwati; Andi Basuki Prima Birawa (Indonesian Association of Clinical Pathologist and Medical laboratory, 2015)
The brain blood flow blockage in ischemic stroke increased oxidative stress and free radicals that cause neurotic cells damage.Computed Tomography Scanning (CT scan) assesses the brain structural damage but not the brain cells damage quantitatively. Adiscrepancy between CT scanand clinical symptoms of ischemic stroke patient is often found. 8-Hydroxy-2-Deoxyguanosine (8-OHdG)serum concentrationis the result offree radical interaction with the cluster C8guanine bases, was used to assess the degree ofneuron cellsdamage, oxidative stress levels. Increase of 8-OHdG serum concentration indicates brain cellsdamage as reflected in the neurologicaldeficitsby the The National Institutes of Health Stroke Scale (NIHSS). The aim of this study was to know the correlation of 8-OHdG serumconcentration with the determination of the degree of neurological deficitby NIHSS inischemic stroke patients. Seventy-two patients withacute ischemic stroke were enrolled in the Dr. Hasan Sadikin Hospital from August 2013 to January 2014. The research was carriedout by cross sectional study design. Statistical analysis was performed by Kruskal-Wallis test, rank Spearman’s correlation test. Mildneurological deficit with a median of 8-OHdG serum concentrations was 3.9 ng/mL (3.3−12.0 ng/mL), moderate neurological deficitwas 23 ng/mL (8.0−51.0 ng/mL) and the severe neurological deficit was 77.5 ng/mL (54.0−97.0 ng/mL). The correlation of 8-OHdGserum concentration with neurological deficits in acute ischemic stroke was 0.912 (p<0.001. Correlation of serum 8-OHdG concentrationwith neurological deficits in acute ischemic stroke was 0.912 (p<0.001). Based on this study result it can be concluded, that this researchhas a strong meaningful positive correlation of 8-OHdG serum concentration with neurological deficits as examined by NIHSS. Inconclusion, serum 8-OHdG has a strong meaningful positive correlation with neurological deficits. 8-OHdG serum concentration can beconsidered to be used to assess discrepancy between CT scan and clinical symptoms as well in health facilities without CT scan.